Implementation of an integrated multispecialty poison-control centre in Bangalore, India: results of a pilot implementation. (April 2017) - Erickson, Timothy B; Wahl, Michael; Hryhorczuk, Daniel; Ramesh, Aruna; Shetty, Naresh; Varghese, Prinston; Prabhakar, Bellur
Abstract: Background: Poisoning accounts for 30% of suicides in India and accidental and environmental exposures to poisons are frequent. The most common poisonings in India involve insecticides, rodenticides, snakebites, alcohols, sedative hypnotics, opioids, and pain medication. In India in 2017, a few poison information centres exist, but there is no regional integrated poison control and information centre that can be readily accessed by people in the community, where poisonings occur. Here, we describe the implementation of a multispecialty model for an integrated regional poison-control centre in the city of Bangalore, Karnataka. Methods: We developed a model for a poison control centre that includes specialists from emergency medicine, critical care, pharmacology, paediatrics, psychiatry, preventive medicine, and laboratory diagnostics. The centre provides referral and management advice for poisonings, drug information, psychosocial care with suicide prevention, forensic medicine, and poison education for the general public. Patients are initially treated and stabilised at peripheral hospitals and then transferred by paramedics to a toxicology centre of excellence, or hospital, for poisoning consultation, intensive care management, enhanced elimination measures, and antidote therapy. Computerised software treatment modules have been developed for the most common poisonings for use by health-care providers in other hospitals in Bangalore. Findings: In 2016, a toxicology centre of excellence was established at the MS Ramaiah Memorial Hospital and Medical College, a major metropolitan hospital in Bangalore, and linked with five peripheral hospitals in Karnataka. The central hospital provides all-hours, low-cost comprehensive poisoning information software and treatment protocols, forensic toxicology testing, reference laboratory analysis, Hazmat decontamination, intensive care management, and an antidote depot for peripheral hospitals. Interpretation: An integrated multispecialty poison control system has been established for the treatment of poisoning in one defined area of a major metropolitan region in India. The project provides poisoning information and a referral system to other surrounding metropolitan hospitals and will soon be rolled out to the entire city of Bangalore (population 10 million people). In response to findings from this pilot phase, we have added more software modules to include treatment of the most commonly encountered poisons. In response to the high rate of intentional poisonings, a suicide prevention and referral centre is being developed and will be located in the same building as the poison control centre. The next phase of the project will include a mobile telecommunications service to the general public in Karnataka (population 65 million). This system of care could be adopted as a model for other states in India to provide affordable, life-saving poison control information, toxicology surveillance, treatment, referral, and poisoning prevention. Funding: MS Ramaiah University.